First molecular detection of zoonotic Plasmodium knowlesi, Plasmodium cynomolgi, and Plasmodium inui in Assamese macaques from northern Thailand - Phakorn Wilaisri; Supakarn Kaewchot; Rucksak Rucksaken; Thitichai Jarudecha; Thanawat Hmaidee; Sakulchit Wichainchot; Chanapath Thabthimsri; Wanat Sricharern (International Journal for Parasitology: Parasites and Wildlife)
The growing proximity between non-human primates (NHPs) and human communities in Thailand has raised concerns about zoonotic disease transmission. Among these NHPs, Assamese macaques (Macaca assamensis) are understudied in Thailand, particularly regarding their role as reservoirs for zoonotic malaria. The limited data on Plasmodium infections in this species highlights the need for further investigation. Therefore, this study determined the prevalence and molecular characterization of zoonotic Plasmodium spp. in Assamese macaques from Chiang Rai Province, northern Thailand. In total, 133 blood samples were collected from Assamese macaques at Tham Pla temple and examined using semi-nested Polymerase Chain Reaction (PCR) targeting the 18S rRNA gene. Plasmodium spp. DNA was detected in 32 samples (24.06 % 32/133; 95 % CI: 17.07–32.23), with nucleotide sequence analysis identifying P. knowlesi in 13.53 % (18/133; 95 % CI: 8.23–20.56), P. cynomolgi in 9.77 % (13/133; 95 % CI: 5.29–16.10), and P. inui in 0.75 % (1/133; 95 % CI: 0.02–4.09). To the best of our knowledge, this was the first molecular evidence of these zoonotic Plasmodium spp. infections in Assamese macaques in Thailand. These findings have highlighted the potential role of Assamese macaques as natural reservoirs for zoonotic Plasmodium species and have underscored the importance of continued surveillance. The data from this study should be beneficial in guiding future strategies to prevent and control simian malaria transmission from macaques to humans.